Effect of the Synthesis Methods on Hydrophobic Properties of Modified Silicas - Olena V. Goncharuk; Iryna Ya. Sulym; Konrad Terpilowski; Evgeniy M. Pakhlov (Adsorption Science & Technology)
Composites based on fumed silica with surface hydrophobic groups were synthesized by chemical substitution of silanol groups' proton for trimethylsilyl (TMS) groups, adsorption of poly(dimethylsiloxane) (PDMS) and combined chemical-adsorption methods. Microcalorimetry measurements and values of the wetting contact angle with water (Θ) were obtained to investigate the hydrophobic properties of prepared materials. The hydrophilicity indexes (K h ) were determined from the relationship of heat of immersion in water Q w to non-polar decane Q d . The Θ and Q w demonstrated changes with increase of modification degree (d m ) for composites containing a monolayer of PDMS. All samples with excess of PDMS had high Θ (>110°) and relatively low Q w and K h . Composites modified with TMS groups demonstrated hydrophobic properties in accordance with K h at d m 0.7, whereas Θ > 90° is observed only for those samples with d m = 1.0. The different methods of synthesis may be applied based on the morphological characteristics and hydrophobicity of the samples.